2013
DOI: 10.5935/abc.20130186
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin and Cardiometabolic Risk in Patients with Acute Coronary Syndromes

Abstract: BackgroundThe adipose tissue is considered not only a storable energy source, but mainly an endocrine organ that secretes several cytokines. Adiponectin, a novel protein similar to collagen, has been found to be an adipocyte-specific cytokine and a promising cardiovascular risk marker.ObjectivesTo evaluate the association between serum adiponectin levels and the risk for cardiovascular events in patients with acute coronary syndromes (ACS), as well as the correlations between adiponectin and metabolic, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The results of this study showed significant paradoxical alterations of serum leptin levels, and non-significant changes in serum adiponectin levels in patients with ischaemic heart disease. Cardio-metabolic risk factors in terms of overweight-obesity and abnormal lipid profile (high fasting serum triglycerides and low high-density lipoprotein) were detected in considerable percent and in agreement with other studies [19,20]. The data of coronary calcium score revealed, that 18 patients were at risk of future myocardial infarction.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study showed significant paradoxical alterations of serum leptin levels, and non-significant changes in serum adiponectin levels in patients with ischaemic heart disease. Cardio-metabolic risk factors in terms of overweight-obesity and abnormal lipid profile (high fasting serum triglycerides and low high-density lipoprotein) were detected in considerable percent and in agreement with other studies [19,20]. The data of coronary calcium score revealed, that 18 patients were at risk of future myocardial infarction.…”
Section: Discussionsupporting
confidence: 89%
“…8 Similarly, a study which was done in Brazil by Gustavo et al, who included the patients with acute coronary syndrome found out reduced adiponectin levels in the cases and also showed the prognostic importance of serum adiponectin level for further cardiovascular events. 9 The relation between serum adiponectin level and central obesity was more specific and was not totally dependent on BMI as patient with normal BMI had significantly raised waist to hip ratio and reduced serum adiponectin level as was indicated in a study done by Chiara et al, who said that hypoadiponectinemia played an important role in metabolic syndrome and cardiovascular disease. 10 Hence it was observed from the study that serum adiponectin level was decreased in patients with acute coronary syndrome and even more reduction of adiponectin level was found in ACS patients with central obesity.…”
Section: Discussionmentioning
confidence: 91%
“…Several clinical trials have suggested an inverse correlation of circulating APN level with adverse outcomes in patients with AMI . However, the results of other studies are contradictory . Animal studies showed that myocardial ischemia/reperfusion (MI/R) injury was severe in the APN knockout mice, which was ameliorated by administering exogenous APN .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 But the relationship between plasma APN level and prognosis of AMI remains controversial. [3][4][5][6][7][8][9] Several clinical trials have suggested an inverse correlation of circulating APN level with adverse outcomes in patients with AMI. [7][8][9] However, the results of other studies are contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation